COVID-19 Metaphors in Philippine Online News Articles - Andrian T Hernandez; Ronilyn V. Ayhon; Jessa F. Balingasa; Darlene B. Bolina; Mark Philip C. Paderan (Universitas PGRI Semarang, 2023)
This study aimed to determine the COVID-19 metaphors in Philippine online news articles. The researchers formulated two main questions in this study: (1) What metaphors are used in online news articles during COVID-19? (2) What are the function and types of these metaphors used in online news articles during COVID-19? To answer the research question, the researchers utilized a qualitative design. A corpus of five news organizations published from March 2020 to February 2021 was gathered to evaluate the metaphors used in online news articles. The needed data was analyzed and extracted using AntConc and the frameworks Critical Metaphor analysis by Charetris-Black (2004) and the Schema Theory by Frederic Bartlett (1932). The study substantiates that “COVID-19: A pandemic of neglect” and ‘COVID-19 is an Enemy” are extremely used in the Philippine online news article. Albeit, other metaphors are also used, such as COVID-19 is Fresh, COVID-19 is a Challenge, and COVID-19 is Contagious and Widespread. The findings also reveal that the metaphors used in online news articles reflect the types of structural metaphor and function as cognitive function. Furthermore, the used metaphors prove that news writers are straightforward in delivering COVID-19 news primarily on the governments handling the pandemic.